2015
DOI: 10.1002/anie.201505063
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Anthranilate Synthase into Isochorismate Synthase: Implications for the Evolution of Chorismate‐Utilizing Enzymes

Abstract: Chorismate-utilizing enzymes play a vital role in the biosynthesis of metabolites in plants as well as free-living and infectious microorganisms. Among these enzymes are the homologous primary metabolic anthranilate synthase (AS) and secondary metabolic isochorismate synthase (ICS). Both catalyze mechanistically related reactions by using ammonia and water as nucleophiles, respectively. We report that the nucleophile specificity of AS can be extended from ammonia to water by just two amino acid exchanges in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(40 citation statements)
references
References 14 publications
2
38
0
Order By: Relevance
“…6B). A protein alignment of the A. fumigatus IcsA and TrpE with characterized bacterial ASS-I and isochorismate synthases revealed that important residues that changed enzymatic activity of the Salmonella typhimorium ASS-I from producing anthranilate to isochorismate (Plach et al, 2015) are identical to the A. fumigatus IcsA, suggesting that it likely is responsible for isochorismate formation although we did not identify this metabolite in our study. Identification of the putative IcsA metabolic product will be a future task.…”
Section: Discussionmentioning
confidence: 65%
“…6B). A protein alignment of the A. fumigatus IcsA and TrpE with characterized bacterial ASS-I and isochorismate synthases revealed that important residues that changed enzymatic activity of the Salmonella typhimorium ASS-I from producing anthranilate to isochorismate (Plach et al, 2015) are identical to the A. fumigatus IcsA, suggesting that it likely is responsible for isochorismate formation although we did not identify this metabolite in our study. Identification of the putative IcsA metabolic product will be a future task.…”
Section: Discussionmentioning
confidence: 65%
“…Networks were visualized with the organic y-files layout in Cytoscape 3.2.0 [ 29 , 30 ]. Phylum-specific sequence sets were compiled from the SSN and used to compute sequence logos of the active site residues, essentially as described [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Anthranilate synthase is considered to share evolutionary origins with other chorismate-metabolizing enzymes such as salicylate synthase (EC 4.2.99.21), aminodeoxychorismate synthase (ACDS) (EC 2.6.1.85) and isochorismate synthase (ICS) (EC 5.4.4.2), owing to similarities in reaction chemistry and polypeptide folding (Bulloch et al, 2004 ; He et al, 2004 ; He and Toney, 2006 ). It has been shown that S. typhimurium AS can accommodate water as a nucleophile (as in ICS) instead of ammonia, thereby displaying a bifunctional AS/ICS activity (Plach et al, 2015 ). Another study demonstrated that only a few mutations were sufficient to induce AS activity in an aminodeoxychorismate synthase, which in its native form does not eliminate pyruvate (Culbertson et al, 2015 ).…”
Section: The Biosynthesis Of Aaamentioning
confidence: 99%